The Development Of Children’s Story Book Media Based On Oral Story Of Local Tradition To Support The Literacy Program For Kindergarten Level - Syefriani Darnis (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
Reading is one of the most fundamental skills a child needs to learn to succeed in life. Developing good reading habits is vital to your child’s future not just academically, but in everyday life as well. It is responsible of all parties , parents, school and government or child care observer in improving the ability children’s reading . In the other hand, there are large number of children’s story books which are labeled according to the age and level of the child’s own development, but in fact incompatible with their age. The children’s story books in the form of short stories, novels or comics are dominated by foreign markets such as Walt Disney series, Japan comics series , and many more. This is one of the reasons why the theme of this study is selected . Children need to be given reading materials that are appropriate with their age and closed to their tradition so young learners have a responsibility towards the surrounding environment and they also grow their love for the region they live in. One of the best resources for reading material is story book based on oral story of local tradition.The purpose of this research is to develop the oral story of local tradition from Samiran village, Selo sub- district, Central Java to supporting the literacy program especially in reading. The research applied was Research and Development and located in Samiran village Central Java. The subjects of this study was 20 children in Pertiwi Kindergarten Samiran, level Kindergarten B at the aged of 5 – 6 year.